Education Using Module on Fetal Growth in Womb Pregnant Women who Chronic Energy Deficiency in Kendari city - Halijah halijah; Elyasari elyasari; Wahida wahida; Kartini kartini (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
The growth of the fetus in the womb is one indicator that determines fetal well-being. This study aims to assess the influence of education on the care of pregnancy in pregnant women with chronic energy deficiency in Kendari City. This was a quasi-experimental design using the pre and posttests. Group 1 was given the education intervention using module. Group 2 was given the education intervention using MCH book. The research samples were as many as 60 people. Data collection instruments were in the forms of the questionnaire, centimeter tape. The data were analyzed by the Wilcoxon and Kruskal Wallis’ tests. The results showed that Education increases the knowledge of pregnant women about the care of pregnancy. Education increases the attitude of pregnant women about the care of pregnancy. Education improves the behavior of pregnant women about the care of pregnancy.